2015
DOI: 10.4103/0973-1482.147390
|View full text |Cite
|
Sign up to set email alerts
|

Carcinosarcoma of ovary with its various immunohistochemical expression: Report of a rare case

Abstract: Ovarian carcinosarcoma is an extremely rare tumor with an incidence of <2%. A report of such a rare case in a 40-year-old multiparous woman is being presented here. The patient complained of abdominal pain and distension. Abdominal computed tomography revealed a variegated mass in the right adnexal region. The CA-125 level was 1635 U/ml. The patient underwent laparotomy and the tumor was removed. Microscopic examination of the tumor showed presence of both carcinomatous and sarcomatous elements. Immunohistoche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 0 publications
0
13
0
Order By: Relevance
“…According to the combination theory, both the malignant epithelial component and the sarcoma component came from pluripotent stem cells that have divergent differentiation. Finally, the conversion theory suggested that the sarcoma component of the tumor resulted from the evolution of the carcinomatous component of the tumor ( 14 , 15 ).…”
Section: Discussionmentioning
confidence: 99%
“…According to the combination theory, both the malignant epithelial component and the sarcoma component came from pluripotent stem cells that have divergent differentiation. Finally, the conversion theory suggested that the sarcoma component of the tumor resulted from the evolution of the carcinomatous component of the tumor ( 14 , 15 ).…”
Section: Discussionmentioning
confidence: 99%
“…IHC can be used to identify the biphasic population but the studies on overexpression of p53 and Ki67 index as prognostic indicators has not yet shown statistically significant results. 7,8…”
Section: Discussionmentioning
confidence: 99%
“…Some studies believe that OCS occur most commonly in postmenopausal women of low parity and often present with disseminated disease at diagnosis with the average age was 65.5 years (range 55–77 years) [ 1 , 8 ]. However, one patient in 40 years of age were represented by Dasgupta [ 7 ]. Menon et al [ 9 ] showed the age at time of diagnosis of OCS varied from 33 to 70 years with a median age of 51 years.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, CT and / or MRI can provide more comprehensive information in the diagnosis and therapy. To date, numerous studies have focused on histopathological characteristics, clinical manifestations and prognosis of OCS [ 1 , 2 ], by contrast, there have been only scattered case studies that have described the imaging findings [ 3 – 7 ]. The purpose of the present study was to analyze the clinical features, CT and MRI characteristics of OCS, and to describe the pathological features and prognosis.…”
Section: Introductionmentioning
confidence: 99%